2000
DOI: 10.1074/jbc.m000359200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PAX6 Homeodomain Function by the Paired Domain

Abstract: PAX6 is required for proper development of the eye, central nervous system, and nose. PAX6 has two DNA binding domains, a glycine-rich region that links the two DNA binding domains, and a transactivation domain. There is evidence that the different DNA binding domains of PAX6 have different target genes. However, it is not clear if the two DNA binding domains function independently. We have studied the effect of structural changes in the paired domain on the function of PAX6 mediated through its homeodomain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 48 publications
2
41
0
1
Order By: Relevance
“…HeLa cells were transfected with different concentrations of wild-type or R242T mutant expression plasmids together with a luciferase reporter plasmid, containing the HD-binding site P3. 29 Figure 3c and d show the transcriptional activity of the wild-type and R242T mutant, respectively. For both constructs, the transcriptional behaviour is described by a linear regression, and the ratio between the corresponding angular coefficients (R242T/wild-type) was 1.72.…”
Section: Expression Of the R242t Mutant In Eukaryotic Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…HeLa cells were transfected with different concentrations of wild-type or R242T mutant expression plasmids together with a luciferase reporter plasmid, containing the HD-binding site P3. 29 Figure 3c and d show the transcriptional activity of the wild-type and R242T mutant, respectively. For both constructs, the transcriptional behaviour is described by a linear regression, and the ratio between the corresponding angular coefficients (R242T/wild-type) was 1.72.…”
Section: Expression Of the R242t Mutant In Eukaryotic Cellsmentioning
confidence: 99%
“…It has been reported that the HD may influence the DNA-binding properties of the PD. 29 Thus, by using bacterially expressed proteins containing both the PD and the HD (PAX6 2 -271 construct) we tried to assess whether the R242T mutation may affect the PD DNA-binding activity. Figure 1c shows the results of the DNA binding of PAX6 2 -271 peptides: the R242T mutant peptide has the same binding activity as the wild-type PAX6 2 -271 , both to the P3 and Cr oligonucleotides.…”
Section: Dna-binding Assaysmentioning
confidence: 99%
See 3 more Smart Citations